Recommendations for Conducting Research on Athletes (Large-Scale Survey Case Studies) - Kerr, Deborah; Hume, PA; Ackland, TR (Springer Singapore, 2018)
Large-scale surveys of world-class athletes have been conducted at Olympic Games and World Championship events for over 60 years. These projects have provided valuable data for identifying the unique physique characteristics for sports and events. There are many challenges in undertaking these studies, and strong scientific rigour should always underpin such projects. Large-scale surveys of athletes should be conducted to address specific questions, rather than being an opportunistic data collection exercise. Considerable planning needs to go into a large-scale survey to ensure its success, including obtaining all the necessary approvals and support to conduct the project. This chapter outlines the practical steps in the process, including what should be in the research proposal, how to conduct large-scale surveys and how to report the results of the information gained.